Decentralization of Local Finances Management in the Developed Federal and Unitary Countries: Experience for Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the experience of decentralization of local finance management in the current conditions in such countries as the USA, Canada, Germany, France, United Kingdom. On the basis of this experience the necessity of expansion of the fiscal powers of the local communities and regions of Ukraine are grounded. Based on the experience of advanced countries, among other things, the emphasis on reforming the financial system of Ukraine, should be made on increasing the tax power of the local communities as well as the regions (particularly in the redistribution of VAT), and not on the expansion of transfer payments. The processes of strengthening the powers of local management have been held using different schemes in most of EU member states in the recent decades. Thus, to preserve the integrity of the UK, government provided significant fiscal powers to the regions, what is important to consider in Ukraine while implementing the new regional policy. In Germany, in contrast to the previous regulation, the extra revenues from VAT are now allocated to a specific formula and on the following principle: the closer the level of tax revenues per capita of federate state is to the average national level of tax revenues, the less additional revenues from VAT this federal state will receive.In general, the modern international experience confirms the positive impact of fiscal decentralization processes on the economic development of the country and its regions.
Keywords: public finance, local finance, local taxes and fees, local charges, tax decentralization, USA, Canada, Germany, France, Great Britain, Poland, European Union, Ukraine, Donbass